Rate of convergence in the Euler scheme for stochastic differential equations with non-Lipschitz diffusion and Poisson measure - Zubchenko, V. P.; Mishura, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the rate of convergence and some other properties of the Euler scheme for stochastic differential equations with the non-Lipschitz diffusion and the Poisson measure.